Impact of aneurysm diameter, angulation, and device sizing on complete occlusion rates using the woven endobridge (WEB) device: Single center United States experience. Issue 3 (June 2023) - Fortunel, Adisson; Javed, Kainaat; Holland, Ryan; Ahmad, Samuel; Haranhalli, Neil; Altschul, David
Background: The Woven EndoBridge device is a novel treatment option for wide-necked bifurcation intracranial aneurysms (WNBA). While this device has had good results, there remains a subset of WNBA that fail this treatment. The main objective of this study is to identify risk factors that are associated with incomplete occlusion of WEB treated aneurysms at short-term follow up. Methods: This was a retrospective study of 31 patients with intracranial aneurysms who were treated with WEB at a single institution in the USA in 2019–2021. Data was collected via chart review on patient demographics, aneurysm characteristics, procedural details, and occlusion status at six months follow up. Bivariate analyses were performed comparing completely occluded aneurysms with neck remnants and residual aneurysms. Results: 16 (52%) had completely occluded aneurysms while 11 (35%) patients had a neck remnant, and 4 (13%) patients had a residual aneurysm at follow up. Patients with neck remnants and residual aneurysms had aneurysms with a larger diameter. A large aneurysm diameter is an independent risk factor for incomplete occlusion (OR 4.23 95% CI 1.08–16.53 P value = 0.038). Patients with residual aneurysms had an average difference between the aneurysm width and WEB diameter of −0.08mm compared to 1.2 mm in patients with occluded aneurysms. 75% of patients with a residual aneurysm presented with a ruptured aneurysm. Lastly, more patients with a residual aneurysm had an immediate angiographic outcome of incomplete occlusion. Conclusion: Larger aneurysms are at risk for incomplete occlusion status post WEB treatment. Larger, ruptured aneurysms with minimal difference in aneurysm and WEB diameter that fail to occlude immediately post-treatment are more likely to present as residual aneurysms at short-term follow up.